Visualizing the included subject: photography, progress narratives and intellectual disability. Issue 4 (December 2018) - Altermark, Niklas; Edenborg, Emil
Abstract By examining photographic depictions of subjects labeled as 'intellectually disabled', this article theorizes how photography performs the ideological function of producing narratives of historical progression. Recurrent representations of, on the one hand, a dark past of state institutionalization and repression and, on the other hand, the present as a time when intellectually disabled people are active, included and happy, function to locate oppression in a bygone era, which effectively obscures how power has transformed rather than disappeared. This relates to how the narrative break between the past exclusion and present inclusion conceals an inherent paradox in the constitution of intellectually disabled subjectivity; at the same time, members of this group are both included by citizenship and classified as lacking the necessary characteristics of the ideal citizen.